Challenges and opportunities in the voluntary carbon market: how can emerging regulatory frameworks and blockchain technology enhance transparency and credibility in the market - Manarte, Bernardo Miguel Cunha (2022)
This work project presents a comprehensive analysis of the voluntary carbon market, exploring dynamics and frameworks while emphasising the transformative impact of blockchain technology in enhancing transparency and credibility. Conducted in partnership with Celfocus, the research delves into the challenges and potential opportunities within the market, offering novel insights for stakeholder perspectives. Detailing qualitative and quantitative data on the historical market context, the study underscores the market's critical importance in reducing carbon emissions. The findings offer valuable contributions to understanding market mechanisms, associated costs, and possible investment outlooks and opportunities in Europe, Africa, and South America.